2020
DOI: 10.1016/j.ijosm.2019.11.003
|View full text |Cite
|
Sign up to set email alerts
|

Psychological context effects of participant expectation on pain pressure thresholds as an adjunct to cervicothoracic HVLA thrust manipulation: A randomised controlled trial

Abstract: Background: Chronic pain is a growing global and economically costly problem leading the National Health Service (NHS) in the UK to actively search for novel strategies to improve health outcomes. Some trials have shown a benefit when practitioners use a positive communication style, however, much of the available literature investigating the use of positive language to alter patient expectation utilises subjective reports from patients. Objectives: To demonstrate whether positive and negative communication be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 76 publications
(89 reference statements)
0
1
0
Order By: Relevance
“…Some other studies have shown positive outcomes with positive verbal suggestions during high velocity low amplitude thrust manipulation (HVLATM) on cervical and thoracic segments. [29,30] Positive verbal suggestions on pain perception…”
Section: Discussionmentioning
confidence: 99%
“…Some other studies have shown positive outcomes with positive verbal suggestions during high velocity low amplitude thrust manipulation (HVLATM) on cervical and thoracic segments. [29,30] Positive verbal suggestions on pain perception…”
Section: Discussionmentioning
confidence: 99%